Workplace spirituality as determinant of affective commitment and moderating role of religiosity among employees of rural development agencies in Malaysia - Wan Yunan, Wan Rahim (2019)
The main purpose of this study was to examine the relationships between workplace spirituality (according to its three dimensions of meaningful work, sense of community, and value alignment) and affective commitment among employees in four different Rural Development Agencies. The study also examined the possible moderating effects of religiosity on the relationships between workplace spirituality dimensions and affective commitment.